Influence of Sexual Sensation Seeking, Sexual Compulsivity and Sexual Pleasure in Condom Use Among Spanish Youth: Implications for HIV Interventions - M. Dolores Gil-Llario; Estefanía Ruiz-Palomino; Rafael Ballester-Arnal; Vicente Morell-Mengual (Journal of Preventive Medicine And Care, 2016)
Spain is one of the countries with the highest incidence of HIV within the European Union. Multiple and complex factors influence HIV infection in young people. This study aims to determine the influence of sexual sensation seeking, sexual compulsivity and perceived sexual pleasure variables in condom use. A total of 424 heterosexual youth were evaluated (M age = 20.62; SD = 2.62) distributed into a risk group (60.7%) and a no-risk group (39.3%). Sexual Sensation Seeking Scale, AIDS Prevention Questionnaire, Sexual Compulsivity Scale, and Sexual Pleasure Perceived Scale were administered. Results indicate statistically significant differences in sexual sensation seeking (p=.001), failure to control sexual impulses (p=.030), perceived sexual pleasure with a condom (p=.027) and without a condom (p=.001). The regression analysis revealed that three factors explained about 14% of the variance in condom use: sexual sensation seeking and sexual pleasure perceived without a condom (risk factors), and sexual pleasure perceived with a condom (protective factor). It is necessary to incorporate these variables into HIV prevention programs to reduce the number of infections in young people.
Keywords: Sexual sensation seeking